2017
DOI: 10.1002/1873-3468.12886
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Aspergillus fumigatus PkaR impacts growth and cell wall integrity through novel mechanisms

Abstract: PKA signaling is essential for growth and virulence of the fungal pathogen Aspergillus fumigatus. Little is known concerning the regulation of this pathway in filamentous fungi. Employing LC-MS/MS, we identified novel phosphorylation sites on the regulatory subunit PkaR, distinct from those previously identified in mammals and yeasts, and demonstrated the importance of two phosphorylation clusters for hyphal growth and cell wall stress response. We also identified key differences in the regulation of PKA subce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…cerevisiae, Schizosaccharomyces pombe, C. neoformans, and Mucor circinelloides and demonstrated that they are downregulated in the presence of the noncompetitive β-1,3-glucan synthase inhibitor caspofungin (64). These authors also constructed a strain in which both phosphorylation sites were mutated (PkaR S24A S39A ) and observed that this strain had reduced radial growth (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cerevisiae, Schizosaccharomyces pombe, C. neoformans, and Mucor circinelloides and demonstrated that they are downregulated in the presence of the noncompetitive β-1,3-glucan synthase inhibitor caspofungin (64). These authors also constructed a strain in which both phosphorylation sites were mutated (PkaR S24A S39A ) and observed that this strain had reduced radial growth (64).…”
Section: Discussionmentioning
confidence: 99%
“…neoformans, and Mucor circinelloides and demonstrated that they are downregulated in the presence of the noncompetitive β-1,3-glucan synthase inhibitor caspofungin (64). These authors also constructed a strain in which both phosphorylation sites were mutated (PkaR S24A S39A ) and observed that this strain had reduced radial growth (64). The exact mechanism underlying PKA activity regulation and phosphorylation in the presence of different environmental cues remains subject to further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In Aspergillus fumigatus , the phosphorylation of PkaR is essential for hyphal growth and cell wall integrity, highlighting that specific phosphorylation by PKA governs numerous processes in fungi [59] . Notably, different studies have indicated the existence of a relationship between the signaling pathway activated by PKA and the carbon source used by fungi [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although PKA signalling is inhibited during cell wall stress in S. cerevisiae (García et al, 2017(García et al, , 2019, positive regulation of the cell wall stress response through crosstalk between the CWI and PKA pathways was identified in Cryptococcus neoformans (Donlin et al, 2014). Furthermore, PKA has been shown to facilitate cell wall remodelling in response to cell wall and osmotic stress in A. fumigatus through its involvement in carbohydrate mobilization in conjunction with the high osmolarity glycerol (HOG) pathway (de Assis et al, 2018;Shwab et al, 2017). This provides a potential mechanism by which PKA signalling may contribute to the response to cell wall and osmotic stress in Z. tritici.…”
Section: Discussionmentioning
confidence: 99%